Fast, low-pressure, low-temperature microwave synthesis of ABW cesium aluminosilicate zeolite nanocatalyst in organotemplate-free hydrogel system. (February 2020) - Ghrear, Tamara Mahmoud Ali; Cheong, Ying-Wai; Lim, Gin Keat; Chateigner, Daniel; Ling, Tau Chuan; Tan, Soon Huat; Ng, Eng-Poh
Graphical abstract: Highlights: Microwave synthesis of organotemplate-free nanoscale Cs-ABW is reported. The nanocrystals are formed from 6 min onwards at 180 °C and ∼20 bar. The nanocrystals (∼68 nm, Si/Al = 1.08) have orthorhombic structure (space group Pc21n ). The nanocrystals are active in cyanoethylation of aliphatic alcohols and is recyclable. Nanosized Cs-ABW had equal or better reactivity than other reported solid base catalysts. Abstract: Cs-ABW zeolite nanocrystals were synthesized using a microwave-assisted hydrothermal technique without an organic template. Using powder X-ray diffraction Rietveld refinement and spectroscopy, we found that pure ABW-type CsAlSiO4 zeolite nanocrystals (Si/Al ratio = 1.08) with an orthorhombic structure (space group Pc21n, a = 9.4425(21) Å; b = 5.4437(11) Å; c = 8.9152(19) Å) can be crystallized from a clear precursor solution of 4SiO2 :1Al2 O3 :16Cs2 O:160H2 O (180 °C, 6 min). The Cs-ABW nanoparticles had a mean particle size of 68 nm and were thermally and colloidally stable. The nanocrystals—which had high accessible basic sites, (Si–O–Al) − Cs +, located at their external surface—were active in catalyzing the cyanoethylation of aliphatic alcohols under non-microwave instant heating, with 100 % selectivity to the desired product and high catalyst reusability. Furthermore, the cyanoethylation of methanol catalyzed by nanocrystalline Cs-ABW under instant heating had equal or better reactivity than those catalyzed by other solid base catalysts.